Percutaneous Tibial Nerve Stimulation in Diabetic and Nondiabetic Women With Overactive Bladder Syndrome: A Retrospective Cohort Study. Issue 11 (30th November 2021) - Zeno, Aldene; Handler, Stephanie J.; Jakus-Waldman, Sharon; Yazdany, Tajnoos; Nguyen, John N.
Abstract : Objectives: The primary objective of this study was to compare optimal response ("very much better" or "much better" on the Patient Global Impression of Improvement [PGI-I] index) to posterior tibial nerve stimulation (PTNS) for overactive bladder (OAB) in patients with and without diabetes mellitus. Secondary outcomes included longitudinal data regarding PTNS use in patients with diabetes and controls. Methods: We performed a retrospective cohort analysis of women in our tertiary care center who completed at least 10 weekly and 1 maintenance PTNS treatments for OAB, excluding patients who were treated with PTNS for a non-OAB primary diagnosis. Participants were grouped into those with diabetes mellitus and those without. Previous research demonstrated a 20% difference in subjective response to anticholinergics in persons with diabetes versus persons without diabetes with OAB. To demonstrate a 20% difference in optimal PGI-I with 80% power, our analysis required 92 patients in each group. Results: We identified 356 patients: 96 with diabetes mellitus, and 260 controls. There was no statistically significant difference in the primary outcome, with 43 (44.8%) of 96 persons with diabetes versus 115 (44.2%) of 260 controls demonstrating optimal PGI-I response ( P = 0.92). Among patients with diabetes, no baseline variables were found to predict treatment response, including hemoglobin A1c greater than 7%, diabetes with sequelae, or higher Charlson Comorbidity Index. Conclusions: In women undergoing PTNS for OAB, the optimal PGI-I response rate is similar in patients with and without diabetes.